Gender Sensitivity among selected students of University of the Philippines Visayas Tacloban College (UPVTC) and the Eastern Visayas State University (EVSU), SY 2008-2009 A preliminary assessment. - Catilogo, Konnie Reika R.; Yanos, Jonnalyn Fil C. (Konnie Reika R. Catilogo, 2009)
This study is entitled "Gender Sensitivity Among Selected Students of the University of the Philippines Visayas Tacloban College (UPVTC) and the Eastern Visayas State University (EVSU), SY 2008-2009 A Preliminary Assessment." This specifically seeks to answer the following questions: 1.) Is there a difference in the level of gender sensitivity between students (UPVTC) who had taken gender sensitive courses from those students (EVSU) who have not? and 2.) Who is more gender sensitive? Is it the male or the female respondents? Is there a difference in the level of gender sensitivity of the male and female? The researchers hypothesized that: Ho:X1 = X2 or there is no significant difference on the level of gender sensitivity between both schools whether they took gender sensitivity courses on the past; H1: X1 not equal to X2 or there is a significant difference on the level of gender sensitivity of the students from both schools; and H0:Xm = Xf or there is no significant difference on the level of gender sensitivity between male and female H1:Xm is not equal to Xf or there is a significant difference on the level of gender sensitivity between male and female.